Thermodynamic Properties Determination in LiF-CaF2 Using Electrochemistry in High Temperature Fused Salts: Application to CeF3. (7th July 2017) - Gibilaro, Mathieu; Massot, Laurent; Chamelot, Pierre
Abstract : Combining thermodynamic database and electrochemical measurements, CeF3 thermodynamics properties were determined between 1113K and 1233K in LiF-CaF2 solution. First, standard potentials of CeF3 /Ce were calculated in different reference states: liquid and solid, and infinite dilution. Then activity coefficients of CeF3 were estimated in the different reference states and for different composition scales: molarity, molality and molar fraction. Finally, constants which interconnected the infinite dilution reference state and the solid and liquid reference states were evaluated.